2021
DOI: 10.1158/1538-7445.sabcs20-pd14-09
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD14-09: Nci 10013 - A randomized phase 2 study of neoadjuvant carboplatin and paclitaxel, with or without atezolizumab in triple negative breast cancer (TNBC)

Abstract: Background Inhibition of PD-L1 with atezolizumab combined with chemotherapy has shown acceptable safety and improved survival in patients with metastatic PD-L1 positive triple negative breast cancer (TNBC). Patients with TNBC who do not achieve a pathological complete response (pCR) to neoadjuvant chemotherapy have a high risk of disease recurrence and death. This randomized, open-label, phase 2 trial evaluates neoadjuvant carboplatin and paclitaxel with or without atezolizumab in patients with previously untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Through comprehensive database retrieval, a total of 983 research records were determined. According to the inclusion and exclusion criteria, six studies with 2,142 patients were included in this meta-analysis; four studies had full text [17][18][19][20], and two studies were published in the form of abstracts (NeoTRIPaPDL1 and Nci 10013 ) [21][22]. Figure 1 A total of six RCTs were included in this meta-analysis, and the characteristics of each study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Through comprehensive database retrieval, a total of 983 research records were determined. According to the inclusion and exclusion criteria, six studies with 2,142 patients were included in this meta-analysis; four studies had full text [17][18][19][20], and two studies were published in the form of abstracts (NeoTRIPaPDL1 and Nci 10013 ) [21][22]. Figure 1 A total of six RCTs were included in this meta-analysis, and the characteristics of each study are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…There were six RCTs included in our meta-analysis (N = 2142) [17][18][19][20][21][22], and the results showed that immunotherapy combined with chemotherapy signi cantly improved pCR rates (OR: 1.91; 95% CI: 1.32-2.78, P < 0.001). The pCR rates were increased by 16.5% in IMpassion031, [20]13.6% in KEYNOTE-522 17 , and 36.8% in Nci 10013 [22]. However, the negative result in NeoTRIPaPDL1 [21] may be associated with the enrolled population being at high risk, the disease stage being late, and the immune induction effect of the chemotherapy regimens in the study design being insu cient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations